1993
DOI: 10.1130/spe284-p303
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Saharan dust to the Central Mediterranean Basin

Abstract: The Mediterranean Basin receives sedimentary contributions from several sources with different geological characteristics. The most important natural source of dust is the Saharan desert. Data from aerosol dust samples collected in a remote site in the Central Mediterranean Basin were used to investigate incursions of Saharan dust during a seven-month period (October-April). This paper is an attempt to trace source areas and transport of dust plumes by means of grain-size, mineralogical, and chemical analyses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
3

Year Published

1995
1995
2002
2002

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 25 publications
3
41
0
3
Order By: Relevance
“…Surface soil samples were collected under clean conditions, in southern Algeria, a region considered to be a significant source of Saharan dust for the western Mediterranean Sea (Bergametti et al 1989;Molinaroli et al 1993). Sampling sites were chosen on the basis of their isolation from any contamination sources (see details and location in Guieu and Thomas 1996).…”
Section: Characterization Of Saharan Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface soil samples were collected under clean conditions, in southern Algeria, a region considered to be a significant source of Saharan dust for the western Mediterranean Sea (Bergametti et al 1989;Molinaroli et al 1993). Sampling sites were chosen on the basis of their isolation from any contamination sources (see details and location in Guieu and Thomas 1996).…”
Section: Characterization Of Saharan Soilmentioning
confidence: 99%
“…Grain size distribution-After a long-range transport across the Mediterranean (1000-2000 km away from the source), the size distribution of Saharan dust shifts to particles Ͻ20 m in diameter (Schütz and Sebert 1987;Molinaroli et al 1993;Guieu et al in press). To be representative of the grain-size distribution of Saharan aerosols, the soil samples were hand sieved in a laminar flow bench, through successive clean polyethylene meshes of 100-and 20-m pore diameter (see arguments and discussion in Guieu et al in press).…”
Section: Characterization Of Saharan Soilmentioning
confidence: 99%
“…Trace metal concentrations were determined by graphite furnace atomic absorption spectrophotometry (GFAAS). Sampling methods, sample treatment and analytical methods are described in detail in Guerzoni et al (1993 (22); 1997 (2) and (23).…”
Section: Trace Metal Analysismentioning
confidence: 99%
“…Previous work (2) has shown that at sites relatively far from pollution sources it is possible to de-couple the desert-derived "end-member" aerosol from the "BKG" component. A multiple approach can be adopted to achieve this: (i) the use of air-mass back trajectories to define source regions (Harris et al, 1982) (25); (ii) the fact that much of the SAH dust over the MED Sea is transported in the form of "pulses", and the identification of these "pulses" offers a potential way of isolating the desert-derived component; (iii) other combined criteria which could be used to classify BKG and SAH aerosols include the use of mineralogical markers (Molinaroli, 1996) (26), Al/Si ratio ) (4) and Ca content ) (23). Finally, for precipitation, (iv) pH values were also used to improve classification, since the alkalinization effect of SAH dust in rain has been well described, both in Sardinia (Caboi et al, 1992 (27); Le Bolloch and Guerzoni, 1995 (28) and elsewhere (Löye-Pilot et al, 1986 (29); Glavas 1988 (30); Roda et al, 1993 (31).…”
Section: Measurement In Air and Rainmentioning
confidence: 99%
“…Trace elements (Cd, Cr, Pb, Zn) in the same samples were analysed in a graphite furnace. Sampling method, sample treatment and analytical methods are described in detail in 1997) and Molinaroli et al (1993). Back-trajectories from the sampling point were computed from analysed wind data along constant pressure surfaces, to help identify the potential source areas of the dust load.…”
Section: Methodsmentioning
confidence: 99%